The complement inhibitor CD59 is required for GABAergic synaptic transmission in the dentate gyrus - Lang Wen; Xiaoli Yang; Zujun Wu; Shumei Fu; Yaxi Zhan; Zuolong Chen; Danlei Bi; Yong Shen (Cell Reports, 2023)
Summary: Complement-dependent microglia pruning of excitatory synapses has been widely reported in physiological and pathological conditions, with few reports concerning pruning of inhibitory synapses or direct regulation of synaptic transmission by complement components. Here, we report that loss of CD59, an important endogenous inhibitor of the complement system, leads to compromised spatial memory performance. Furthermore, CD59 deficiency impairs GABAergic synaptic transmission in the hippocampal dentate gyrus (DG). This depends on regulation of GABA release triggered by Ca2+ influx through voltage-gated calcium channels (VGCCs) rather than inhibitory synaptic pruning by microglia. Notably, CD59 colocalizes with inhibitory pre-synaptic terminals and regulates SNARE complex assembly. Together, these results demonstrate that the complement regulator CD59 plays an important role in normal hippocampal function.